Mycosis fungoides and Sézary syndrome: focus on the current treatment scenario - José Antonio Sanches; Jade Cury-Martins; Rodrigo Martins Abreu; Denis Miyashiro; Juliana Pereira (Sociedade Brasileira de Dermatologia, 2021)
Abstract Cutaneous T-cell lymphomas are a heterogeneous group of lymphoproliferative disorders, characterized by infiltration of the skin by mature malignant T cells. Mycosis fungoides is the most common form of cutaneous T-cell lymphoma, accounting for more than 60% of cases. Mycosis fungoides in the early-stage is generally an indolent disease, progressing slowly from some patches or plaques to more widespread skin involvement. However, 20% to 25% of patients progress to advanced stages, with the development of skin tumors, extracutaneous spread and poor prognosis. Treatment modalities can be divided into two groups: skin-directed therapies and systemic therapies. Therapies targeting the skin include topical agents, phototherapy and radiotherapy. Systemic therapies include biological response modifiers, immunotherapies and chemotherapeutic agents. For early-stage mycosis fungoides, skin-directed therapies are preferred, to control the disease, improve symptoms and quality of life. When refractory or in advanced-stage disease, systemic treatment is necessary. In this article, the authors present a compilation of current treatment options for mycosis fungoides and Sézary syndrome.